2022
DOI: 10.3390/catal12091055
|View full text |Cite
|
Sign up to set email alerts
|

Se-Doped Ni5P4 Nanocatalysts for High-Efficiency Hydrogen Evolution Reaction

Abstract: Increasing energy consumption and environmental pollution problems have forced people to turn their attention to the development and utilization of hydrogen energy, which requires that hydrogen energy can be efficiently prepared. However, the sluggish kinetics of hydrogen evolution reaction (HER) requires higher overpotential. It is urgent to design and fabricate catalysts to drive the procedure and decrease the overpotential of HER. It is well known that platinum catalysts are the best for HER, but their high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…These strategies, as discussed in references, offer avenues for optimizing the performance and efficiency of Ni 2 Se 3 catalysts. [48][49][50][51][52][53] A recent review conducted by Anantharaj et al 54 has presented a comprehensive comparison of Tafel slope values of nickel selenide in electrochemical water oxidation reactions. Their ndings revealed that Tafel values fall within the range of 24 to 128 mV dec −1 across various nanostructures, substrates, and electrolyte conditions.…”
Section: Resultsmentioning
confidence: 99%
“…These strategies, as discussed in references, offer avenues for optimizing the performance and efficiency of Ni 2 Se 3 catalysts. [48][49][50][51][52][53] A recent review conducted by Anantharaj et al 54 has presented a comprehensive comparison of Tafel slope values of nickel selenide in electrochemical water oxidation reactions. Their ndings revealed that Tafel values fall within the range of 24 to 128 mV dec −1 across various nanostructures, substrates, and electrolyte conditions.…”
Section: Resultsmentioning
confidence: 99%
“…17,25 To date, a few studies on transition metal-doped Ni 5 P 4 materials have been reported. These studies demonstrated enhanced HER activity of porous Ni 5 P 4 microstructures doped with Fe, 26,27 Co, 27,28 V, 23 Se, 29 Cu, 27 and Ru 21 in acids and alkali. Under alkaline conditions, Ru doping improved the HER activity by decreasing the η −10 to 123 mV compared to 289 mV for Ni 5 P 4 .…”
Section: ■ Introductionmentioning
confidence: 84%